EFEKTIVITAS PENDEKATAN RESTORATIVE JUSTICE DALAM PENYELESAIAN PERKARA ANAK BERHADAPAN DENGAN HUKUM DI KOTA BANDUNG - Fikarudin, Wildan (Ensiklopedia of Journal, 2025)
Abstract: This research analyzes the effectiveness of the restorative justice approach in resolving cases of children in conflict with the law in Bandung City following the enactment of Law Number 11 of 2012 on the Juvenile Criminal Justice System. Using normative legal methods with statutory, conceptual, and case approaches, the research reveals a significant increase in the application of diversion mechanisms from 65% in 2019 to 72% in 2020, and its effectiveness in preventing  stigmatization, protecting children's rights, and facilitating social reintegration with a  reintegration success rate of 85%. Nevertheless, the implementation of restorative justice still  faces challenges including limitations in comprehensive post-diversion rehabilitation programs, high rotation of trained personnel, disparities in understanding among law enforcement officials, inadequate child placement institutions according to standards, and the persistent retributive paradigm in society. The research recommends regulatory revisions for flexibility in diversion criteria, strengthening institutional capacity and coordination, developing comprehensive  rehabilitation programs, and educating the public to shift from retributive to restorative  paradigms.Keywords: restorative justice, diversion, juvenile criminal justice system, best interest of the child, social reintegration